The effect of a valine to phenylalanine mutation in the precore region of hepatitis b virus on virus replication, HBeag maturation and expression - Chen, Chien- Yu (My University, 2011)
Hepatitis B virus (HBV) infection is endemic in South Africa. A unique feature of HBV carriers in this geographical region is that majority of the carriers are HBV e antigen (HBeAg) negative before they reach adulthood. Up to a few years ago the reason for this early loss of HBeAg was unknown. HBeAg is translated from the precore mRNA whose transcription is controlled by the basic core promoter. The dominant subgenotype of HBV in South Africa is subgenotype A1. This subgenotype is characterized by various variations/mutations in the basic core promoter and precore region of HBV that can affect HBeAg expression. Within the basic core promoter, A1762T/G1764A mutations can affect the expression of HBeAg at the transcriptional level. These mutations interfere with transcription factor binding to the basic core promoter and suppress the transcription of precore mRNA that is translated into HBeAg, hence reducing HBeAg expression. Mutations at nucleotides 1809-1812, also within the basic core promoter, reduce HBeAg expression at the translational level by creating a “sub-optimal” Kozak sequence upstream from the precore start codon at position 1814 from the EcoRI site. Following translation of the precore/core fusion protein, this precursor molecule of HBeAg is post-translationally modified by signal peptide cleavage at a fixed site on the amino end and at variable sites on the carboxyl end. The precore/core open reading frame on the precore mRNA that codes for the precursor of HBeAg, overlaps the region that codes for the encapsidation signal (ε) on the pregenomic RNA (pgRNA). pgRNA plays a pivotal role in the initiation of reverse transcription and is translated into the capsid protein and the polymerase enzyme. In previous studies, a guanine (G) to thymine (T) mutation at nucleotide 1862 within the precore region was identified in subgenotype A1 isolates from asymptomatic carriers of the virus and from hepatocellular carcinoma patients from South Africa. This mutation could conceivably have two functional consequences. Firstly, the G1862T mutation could change the secondary structure of ε and could interfere with and hence affect HBV replication. Secondly, the phenotypic change from valine to phenylalanine introduced by the G1862T mutation at codon 17 (-3 position to the signal peptidase recognition motif) is close to the signal peptide cleavage site at position 19 (-1 position to the signal peptidase recognition motif), and may therefore abrogate signal peptide cleavage. Therefore the objective of this study was to functionally characterize the HBV G1862T mutation and its equivalent G1982T found in woodchuck hepatitis virus (WHV). This was done by determining the effect of this mutation on viral replication and eAg expression of plasmid constructs in vitro. Replication competent clones were constructed by mutating the wild-type of HBV and the mutant of WHV. The G1862T and T1982G mutation were introduced into the precore region of replication competent HBV and WHV plasmids, respectively, by site-directed mutagenesis. HBeAg-expression and WHeAg-expression plasmids were constructed using the replication competent clones as templates. For HBV, the templates used belonged to genotype D or to genotype D in which the precore region was mutated into a genotype A context, genotype ‘A’. Huh 7 hepatoma cells were transfected with the respective replication competent clones and HBV replication was followed using Southern hybridization and real time polymerase chain reaction (PCR). The secretion and expression of HBeAg were monitored using enzyme-linked immunosorbent assay (ELISA), immunocytochemistry and confocal microscopy, following transfection with the eAg expressing plasmids. The secretion and expression of WHeAg were monitored using pulsed radioactivelabel, immunoprecipitation, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and immunocytochemistry and confocal microscopy. HBV replication was significantly reduced when the G1862T was introduced into genotype D but not into genotype ‘A’ HBV replication competent constructs. Following transfection with mutated HBeAg-expression plasmids, a reduction of 38 % for genotype D, and 54 % for genotype ‘A’ in HBeAg secretion relative to the wild-type were observed. Using the WHV constructs, reduced processing of the mutant relative to the wild-type protein was demonstrated using pulse-radioactive labelling. Using confocal microscopy it was demonstrated that both the mutant HBeAg and mutant WHeAg accumulated in the endoplasmic reticulum, endoplasmic reticulum Golgi intermediate compartment and Golgi. This accumulation is because the introduction of a phenylalanine at position -3 of the signal peptide cleavage site interfered with the post-translational modification of the HBeAg precursor protein. The aggregates of mutant HBV protein increased in size following treatment of cells with a proteasome inhibitor, MG132, and had the hallmark features of aggresomes. They attracted ubiquitin, heat shock proteins and proteasomes, and were isolated from the cytosol by the intermediate filaments, vimentin and cytokeratin. Aggresomes formed by the HBV mutant precore protein resembled Mallory-Denk bodies which are histological and potential markers of progressive liver diseases.